Implementasi Metode Rational Unified Process (RUP) dalam Pengembangan Sistem Informasi Presensi (SIM-PR) Menggunakan Teknologi QR Code - Andi Muh. Sahirul Haq; Jumadi Mabe Parenreng; Muh Rais; Yasdin Yasdin (Progressive Information, Security, Computer, and Embedded System, 2024)
The attendance system in schools currently still uses a manual system such as wet signatures on paper media. With such a system, there are still shortcomings in terms of efficiency of manpower, cost, and time. Therefore, this study aims to develop an attendance system that uses QR Code technology to be more efficient. In addition, this study aims to test the system using the ISO/IEC 25010 standard as a reference, and to test the QR Code by considering the QR conditions and the scan distance to the system. This study uses the Rational Unified Process (RUP) development method. With this development method, an attendance system was obtained with very good test results and met the ISO/IEC 25010 standards in all existing aspects. In QR Code technology, the ideal distance for scanning is 5 cm - 25 cm from the camera where from various conditions that have been tested, only two QR conditions were found that could not be scanned by the system, including the QR Code covered by foreign objects, and the QR Code in a crumpled condition. Therefore, it can be concluded that the attendance system using QR Code technology that has been created can function well in terms of the system as well as the QR Code.